Reputation: 17
I'm new with algorithms and wonder how this displayed function is supposed to be converted/transformed from recursive to iterative. What should I keep in mind when converting?
public int binom(int n, int k)
{
if (k == 0 || n == k) { return 1; }
return binom(n - 1, k - 1) + binom(n - 1, k);
}
Thanks in advance!
Upvotes: 1
Views: 114
Reputation: 259
In fact, this problem is not so easy, if you just look at the recursive code and try to decrypt it. However, it might be a helpful hint for you, that (n over k), i.e. the binomial coefficient can be written as
n! / (k! * (n - k)!)
where "!" denotes the factorial. And it should be rather easy to compute the factorial in a Loop (i.e. iterative) for you.
If intermediate results are too big you can shorten before computation. You can shorten either term k! or the term (n-k)! (you would choose the bigger one). For example with n = 5 and k = 3 you have: (1 * 2 * 3 * 4 * 5) / ((1 * 2 * 3) * (1 * 2)) = (4 * 5) / (1 * 2)
Spoiler-Alarm:
public static int binomial(int n, int k) {
int nMinusK = n - k;
if (n < nMinusK) {
//Switch n and nMinusK
int temp = n;
n = nMinusK;
nMinusK = temp;
}
int result = 1;
// n!/k!
for (int i = k + 1; i <= n; i++) {
result *= i;
}
//Division by (n-k)!
for (int j = 1; j <= nMinusK; j++) {
result = result / j;
}
return result;
}
Upvotes: 1